Effectiveness of rope jump and single leg jump training towards the leg power and the length of the kick (long pass) of the football players from ssb pesat tempel sleman in the age group of 14-15 years old - Imam Wahyu Nalendra; Tomo, Bangkit Pambudi; Rizky Pratama Galuh Saputra; Najwa Fatullah Arkan Zaky; Haniffan Radeva Naryana; Refaldi Tri Jadmiko; Rahmat Diky Pratama; Gagat Prabantoro; Wisnu Prasetya; Fauzan Pratama (Departement of Sports Coaching, Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2025)
This research aims to determine the effectiveness of rope jump training and single leg jump training towards the increasing leg power and long pass skills of football players from SSB Pesat (Pesat Football School) Tempel, Sleman Regency in the age group of 14-15 years old. This study used a quasiexperimental type for 16 training sessions with a two-group pretest- posttest design research method. The selection of subjects used a purposive sampling technique totaling 20 student samples with group division using the matched subject ordinal pairing technique. The research instrument used a skipping rope for rope jump training and a hurdle for single leg jump training. The data collection technique used a long pass test by Frank M. Verducci with a validity value of 0.94 and a reliability value of 0.99, and a vertical jump test by Bafirman and Wahyuni with a validity value of 0.95 and a reliability value of 0.96. The data analysis technique used prerequisite tests, called normality tests and homogeneity tests, and used a t-test to determine the research hypothesis with a significance level of 5%. The research findings show that 1) rope jump training increase leg power ability, with t count at 6.000 > t table 2.262, significance 0.000 < 0.05, percentage increase at 5.053%, and increasing long pass skills, with t count at 5.288 > t table 2.262, significance 0.001 < 0.05, percentage increase at 2.626%. 2) Single leg jump training increases leg power ability, with t count at 7.571 > t table 2.262, significance 0.000 < 0.05, percentage increases 4.536%, and increasing long pass skills, with t count at 6.181 > t table 2.262, significance 0.000 < 0.05, percentage increases at 2.426%. 3) Rope jump training provides greater improvement compared to single leg jump training on leg power ability and long pass skills of football players from SSB Pesat Tempel Sleman in the age group of 14-15 years old.